2022
DOI: 10.4236/wjcd.2022.126033
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical and Etiological Profile of Rhythmic Emergencies at the University Hospital of Brazzaville, Republic of Congo

Abstract: Objectives: To describe the epidemiological, clinical and etiological aspects of rhythmic emergencies at the University Hospital of Brazzaville. Patients and Methods: This was a retrospective descriptive study conducted in the cardiology and internal medicine department of the University Hospital of Brazzaville from January 1, 2014 to June 30, 2016. Were included, all patients admitted for a severe rhythm disorder diagnosed on the surface electrocardiogram. Rhythmic emergency was defined as a severe rhythm dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Further on, in 2009 Kimbally et al reported a mean age of 37.5 years with a male predominance [14]. This difference in results could be explained by the methodology used in the last 2 studies.…”
Section: Socio-demographic Characteristics Of Participantsmentioning
confidence: 98%
See 2 more Smart Citations
“…Further on, in 2009 Kimbally et al reported a mean age of 37.5 years with a male predominance [14]. This difference in results could be explained by the methodology used in the last 2 studies.…”
Section: Socio-demographic Characteristics Of Participantsmentioning
confidence: 98%
“…The previous studies were carried out in urban areas; the Kimbally study used the WHO STEPS approach. [14] and that of Ellenga Mbolla [15] screening in non-hospital settings [15]. This contrast raises the question of awareness and management of hypertension, a genuine global public health problem.…”
Section: Socio-demographic Characteristics Of Participantsmentioning
confidence: 99%
See 1 more Smart Citation